2018
DOI: 10.21475/ajcs.18.12.06.pne1213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different sources of pollen on the chemical composition of date (Phoenix dactylifera L.) cultivar Medjool in México

Abstract: The objective of the present work was to investigate the influence of pollen sources over chemical characteristics of the Medjool date cultivar. The study was conducted under conditions of the Northwest part of Mexico, during the year 2016 cultivation season. The content of nutrients (protein, lipids, fiber and ash), sugars (total, reducing, non-reducing, sucrose, glucose and fructose), and most abundant minerals were evaluated. Three bunches of each of the four selected female palms Medjool cultivar were poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
12
3
2
Order By: Relevance
“…The insoluble solids content on average for this study was 94.64 g/100 g for the seed (Table 3), much higher than the pulp content of the same fruit (15.70 g/100 g) reported in another study under the same production conditions [12]. The average of the four treatments in total soluble solids and total acidity of 'Medjool' seeds were lower than the results reported for fruit by the study mentioned above; however, the pH turned out to be very similar to that of the 'Medjool' date fruit [12].…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…The insoluble solids content on average for this study was 94.64 g/100 g for the seed (Table 3), much higher than the pulp content of the same fruit (15.70 g/100 g) reported in another study under the same production conditions [12]. The average of the four treatments in total soluble solids and total acidity of 'Medjool' seeds were lower than the results reported for fruit by the study mentioned above; however, the pH turned out to be very similar to that of the 'Medjool' date fruit [12].…”
Section: Discussioncontrasting
confidence: 62%
“…Table 8 shows the average values of the physical parameters and proximal composition of 'Medjool' date seeds obtained from the four treatments (pollen sources: 'Deglet Noor', 'Khadrawy', 'Medjool', and 'Zahidi') in this study compared to those reported by studies carried out in Morocco [30] and United Arab Emirates [31]. The insoluble solids content on average for this study was 94.64 g/100 g for the seed (Table 3), much higher than the pulp content of the same fruit (15.70 g/100 g) reported in another study under the same production conditions [12]. The average of the four treatments in total soluble solids and total acidity of 'Medjool' seeds were lower than the results reported for fruit by the study mentioned above; however, the pH turned out to be very similar to that of the 'Medjool' date fruit [12].…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations